Selective Brain Hypothermia in Acute Ischemic Stroke: Reperfusion Without Reperfusion Injury - Choi, Jae H.; Poli, Sven; Chen, Michael; Nguyen, Thanh N.; Saver, Jeffrey L.; Matouk, Charles; Pile-Spellman, John (Frontiers in Neurology, 2020)
In acute ischemic stroke, early recanalization of the occluded artery is crucial for best outcome to be achieved. Recanalization aims at restoring blood flow to the ischemic tissue (reperfusion) and is achieved with pharmacological thrombolytic drugs, endovascular thrombectomy (EVT) devices, or both. The introduction of modern endovascular devices has led to tremendous anatomical and clinical success with rates of substantial reperfusion exceeding 80% and proven clinical benefit in patients with anterior circulation large vessel occlusions (LVOs). However, not every successful reperfusion procedure leads to the desired clinical outcome. In fact, the rate of non-disabled outcome at 3 months with current EVT treatment is approximately 1 out of 4. A constraint upon better outcomes is that reperfusion, though resolving ischemic stress, may not restore the anatomic structures and metabolic functions of ischemic tissue to their baseline states. In fact, ischemia triggers a complex cascade of destructive mechanisms that can sometimes be exacerbated rather than alleviated by reperfusion therapy. Such reperfusion injury may cause infarct progression, intracranial hemorrhage, and unfavorable outcome. Therapeutic hypothermia has been shown to have a favorable impact on the molecular elaboration of ischemic injury, but systemic hypothermia is limited by slow speed of attaining target temperatures and clinical complications. A novel approach is endovascular delivery of hypothermia to cool the affected brain tissue selectively and rapidly with tight local temperature control, features not available with systemic hypothermia devices. In this perspective article, we discuss the possible benefits of adjunctive selective endovascular brain hypothermia during interventional stroke treatment.